Team Race Game In Teaching Vocabulary Mastery At SMP Negeri 2 Panca Rijang - Nico Bisse; Syamsinar R; Syamsu T; Sam Hermansyah (La Ogi : English Language Journal, 2021)
The objective of the research was to find out whether or not use of team race game can improve the ability of the students of SMP Negeri 2 Panca Rijang in vocabulary. This research employed the method of the research was pre-experimental method with one group pre-test and post-test design. The population was the VII.2 students of SMP Negeri 2 Panca Rijang in 2018-2019 academic years. Total number of population was 99 students consists of 4 classes and class(VII.2) was taken as sample by using team race game, total number of sample was 25. The instrument used in this research was vocabulary test. The result of this research showed that the pre-test got the mean score (34,80) while the post-test got mean score (67,16) . This showed that there was significant difference between pre test and post tes. The result of the P-value(0,000) was lower than level of significant (apha (Î±)=0,05). This means that H1 was accepted. This research concluded that teaching vocabulary by using team race game improved the students ability in vocabulary mastery at the second year of SMP Negeri 2 Panca Rijang. The research data indicated that the applying team race game in vocabulary was significantly improved the vocabulary. The mean score of students interest showed 73,88. It means the students interested to use team race game approach in improving students vocabulary